A Review on the Concept of Avapeedaka Snehapana in the management of Mutravahshroto Dushti - Vishnoi, Naina; Sharma, Mahesh Kumar; Sharma, Gyan Prakash; Sharma, Renu (International Research Journal of Ayurveda & Yoga, 2022)
The ketogenic or “keto” diet is a low-carbohydrate, fat-rich eating plan that has been used for centuries to treat specific medical conditions. In the 19th century, the ketogenic diet was commonly used to help control diabetes. In 1920 it was introduced as an effective treatment for epilepsy in children in whom medication was ineffective. The ketogenic diet has also been tested and used in closely monitored settings for cancer, diabetes, polycystic ovary syndrome, and Alzheimer’s disease. In the Ancient Science of Ayurveda Sneha (lipid) is the essence of an individual and human beings life. Snehana (oleation) has a fundamental role in Ayurveda treatments in both preventive and curative aspect. It can be widely divided into bahya snehana (external oleation) and abhyantara snehana (internal oleation). Snehapana (internal administration of lipid) comes under abhyantara snehana and is the internal administration of Sneha dravya (lipid). Sneha dravya can be taila (oil), ghrita (ghee), majja (bone marrow), and vasa (muscle fat) individually or in combination. Snehapana is the principal treatment to be done prior to sodhana (purificatory procedure) and is one among purvakarma (pre purificatory procedure). On the basis of therapeutics, snehapana can be classified based on their action as brhmana (nourishing), samana (pacifying), and sodhana (purifying). In the Management of Mutravahashroto Dushti(Urinary tract disorder) Avapeedaka snehapana is very helpful.